Frequency Of Hysterosalpingography Findings In Females Presenting With Infertility In Gujrat - Ahmad Mubashar, Burhan; Zulfiqar, Taiba; Ali, Abid; Rashid , Ali (Medical Science Journal for Advance Research, 2022)
Background: Infertility is a gynecological illness which has clinical, financial and psychological consequences that affects 1.3% to 25.7% of couples throughout the world. Hysterosalpingography is a typical imaging technique used in gynecological practice to diagnose infertility in women. Aim And Objective: The objective of our study was to evaluate the frequency of Hysterosalpingography findings in females presenting with infertility in Gujrat. Methodology: The prospective cross sectional study was carried out at X-Ray unit in Azeem Ultrasound & Digital X-Rays center, Gujrat, Pakistan. A total of 90 females patients with infertility were enrolled in present study. The duration of this research work was from February 2022 to May 2022. The data was gathered using a predesigned questionnaire form.. Statistical Package of Social Sciences was used to analyze the data. Frequency of different findings was found out. These were then graphically portrayed in the form of tables and graphs. Results : We observed 90 female patients out of which 72 (80%) patients found to be normal. In 18 (20%) patients fallopian tube blockage was diagnosed. Out of 18 patients, 8 (8.9%) were having right sided fallopian tube blockage, 8(8.9%) were having bilateral tubal blockage while only 2 (2.2%) showed left sided tube block. Hydrosalpinx was found in 4(4.4%) patients and uterine anomaly in 2(2.2%) patients. Conclusion: Fallopian tube blockage and hydrosalpinx were common factors of infertility in our study. Hysterosalpingography provides an easy and affordable source for evaluation of infertility factors.